Impacts of Anthropogenic Activities on Watersheds in a Changing Climate - Pacheco, Fernando A.L; Sanches Fernandes, Luís Filipe (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The immediate goal of this Special Issue was the characterization of land uses and occupations (LULC) in watersheds and the assessment of impacts caused by anthropogenic activities. The goal was immediate because the ultimate purpose was to help bring disturbed watersheds to a better condition or a utopian sustainable status. The steps followed to attain this objective included publishing studies on the understanding of factors and variables that control hydrology and water quality changes in response to human activities. Following this first step, the Special Issue selected work that described adaption measures capable of improving the watershed condition (water availability and quality), namely LULC conversions (e.g., monocultures into agro-forestry systems). Concerning the LULC measures, however, efficacy was questioned unless supported by public programs that force consumers to participate in concomitant costs, because conversions may be viewed as an environmental service.